Seamless requirements. (September 2017) - Naumchev, A.; Meyer, B.
Abstract: Popular notations for functional requirements specifications frequently ignore developers' needs, target specific development models, or require translation of requirements into tests for verification; the results can give out-of-sync or downright incompatible artifacts. Seamless requirements, a new approach to specifying functional requirements, contributes to developers' understanding of requirements and to software quality regardless of the process, while the process itself becomes lighter due to the absence of tests in the presence of formal verification. A development case illustrates these benefits, and a discussion compares seamless requirements to other approaches. Highlights: New software requirements specification technique is proposed called seam-less requirements. A seamless requirement includes formal and natural-language component. The formal component is a proof obligation expressed as a contracted self-contained routine. The natural-language component is a natural-language comment on the routine. Simple example illustrates benefits of the new technique.